Academic Senate Minutes 2003-03-06 - Academic Senate:::::::::
Agenda and all Minutes presented approved. Reports from Chair, President, Provost and Vice President of Administration and Finance. Resolution: Constitutional Amendment regarding Lecturer Senator Term approved. Statement on Mission, Goals, and Objectives of General Education at SSU with one amendment approved. Statement made for Good of the Order.